ADVANCED SIGNAL PROCESSING METHODS FOR RESEARCH ON VIBRATION PROPAGATION IN VEHICLE CONSTRUCTION (Perner's Contacts, 2013)
The article provides a discussion on the studies on advanced signal processing methods for research on vibration propagation in vehicle construction. One of the major purpose of vehicle vibration research is evaluation of the human vibration perception in transport. For this purpose it is necessary to analyse the structure of vibration signals in chosen elements of suspension and car body. The scope of the research allows analysis of quantity of vibration isolation by suspension system and distribution of the vibration penetrates into human body by the feet. The presented algorithm of the signal distribution by the stationary and nonstationary conditions allows proper analysis of the signals separately as the stationar and nonstationar signal.